2018
DOI: 10.3389/fpls.2018.01170
|View full text |Cite
|
Sign up to set email alerts
|

Rhamnolipids From Pseudomonas aeruginosa Are Elicitors Triggering Brassica napus Protection Against Botrytis cinerea Without Physiological Disorders

Abstract: Rhamnolipids (RLs) are amphiphilic molecules naturally produced by some bacteria with a large range of biological activities. Although some studies report their potential interest in plant protection, evaluation of their effects and efficiency on annual crops of worldwide agronomic interest is lacking. The main objective of this work was to investigate their elicitor and protective activities on rapeseed crop species while evaluating their physiological effects. Here we report that RLs from Pseudomonas aerugin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 58 publications
2
55
0
1
Order By: Relevance
“…Natural RLs are known to have direct antimicrobial activities against fungi and zoosporic plant pathogens [ 43 ]. In addition, these RLs are able to affect conidial germination and mycelial growth of the necrotrophic fungus B. cinerea [ 32 , 33 , 34 ]. Based on their eliciting activities, four smRLs including Eth-C10, Eth-C12, Car-C12, and Est-C12 were selected for the following experiments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural RLs are known to have direct antimicrobial activities against fungi and zoosporic plant pathogens [ 43 ]. In addition, these RLs are able to affect conidial germination and mycelial growth of the necrotrophic fungus B. cinerea [ 32 , 33 , 34 ]. Based on their eliciting activities, four smRLs including Eth-C10, Eth-C12, Car-C12, and Est-C12 were selected for the following experiments.…”
Section: Resultsmentioning
confidence: 99%
“…These molecules have direct antimicrobial properties against various fungal species in vitro and in vivo [ 25 , 26 , 27 , 28 , 29 , 30 ]. A number of studies have also reported that natural rhamnolipids are able to stimulate plant immunity and trigger induced resistance against various phytopathogens [ 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pseudomonas aeruginosa Botrytis cinerea Spore germination and mycelial growth inhibition Varnier et al, 2009;Monnier et al, 2018 Rha-Rha-C 10 -C 10 , Rha-C 10 -C 10…”
Section: Lipopeptides As Antimicrobial Agentsmentioning
confidence: 99%
“…Biosurfactants are biomolecules that are amphiphilic in nature and include a large category of glycolipids, lipopeptides phospholipids, fatty acids and polymeric macromolecules [ 8 , 9 ]. Members of genus Pseudomonas are among the front runners in this context and are reported to produce cyclic lipopeptide and rhamnolipid (a type of glycolipid) biosurfactants [ 10 , 11 ]. Biosurfactants are biodegradable, biocompatible, durable in a range of temperatures and pH and are non-toxic in nature [ 9 , 12 ].…”
Section: Introductionmentioning
confidence: 99%